2018
DOI: 10.1016/j.jshs.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Parental social support, perceived competence and enjoyment in school physical activity

Abstract: BackgroundBeginning in the elementary school years, there are differences among children on how they perceive their competence in physical activity (PA). Children's competence perceptions may influence their affective reactions to PA. A crucial question is how to motivate children who hold low competence perceptions to enhance their enjoyment and PA involvement. Because parents play critical roles in children's development and socialization, social support from parents can be an important factor to complement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 36 publications
(40 reference statements)
3
44
1
7
Order By: Relevance
“…Cross-sectional studies have consistently shown that self-efficacy is a mediating variable between social support and PA (Motl, Dishman, Saunders, Dowda, & Pate, 2007; Peterson, Lawman, Wilson, Fairchild, & Van Horn, 2013; Wing, Bélanger, & Brunet, 2016). That is, social support may enhance an individual’s self-efficacy to overcome barriers to PA, and this enhanced self-efficacy is associated with greater PA. Other studies have highlighted that lack of time, lack of interest and enjoyment may also mediate the relationship between social support and PA (Shen et al, 2016; Verloigne et al, 2014; Wing et al, 2016), but these findings are based on only three studies. This suggests that a lack of social support may lead to young people being uninterested in PA and perceive barriers, such as lack of time, to PA.…”
Section: Introductionmentioning
confidence: 96%
“…Cross-sectional studies have consistently shown that self-efficacy is a mediating variable between social support and PA (Motl, Dishman, Saunders, Dowda, & Pate, 2007; Peterson, Lawman, Wilson, Fairchild, & Van Horn, 2013; Wing, Bélanger, & Brunet, 2016). That is, social support may enhance an individual’s self-efficacy to overcome barriers to PA, and this enhanced self-efficacy is associated with greater PA. Other studies have highlighted that lack of time, lack of interest and enjoyment may also mediate the relationship between social support and PA (Shen et al, 2016; Verloigne et al, 2014; Wing et al, 2016), but these findings are based on only three studies. This suggests that a lack of social support may lead to young people being uninterested in PA and perceive barriers, such as lack of time, to PA.…”
Section: Introductionmentioning
confidence: 96%
“…Parental involvement in this capacity may be related to parental support, which has been positively associated with non-Indigenous youth's activity levels (Sterdt et al 2013;Yao and Rhodes 2015). In a study done in the United States, Shen and colleagues found that parental social support could enhance children's enjoyment of participation in physical activity during school hours (Shen et al 2016). Thus, the provision of parental support for and involvement in the development of physical activity programs may foster youth's tendencies to participate in more active behaviours (Kerpan and Humbert 2015;Lavallée and Lévesque 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Las autorizaciones adicionales a las aquí delimitadas se pueden obtener en el correo: educare@una.cr Revista Electrónica Educare (Educare Electronic Journal) EISSN: 1409-4258 Vol. 23(2) MAYO-AGOSTO, 2019:1-18 the family environment has been pointed out by Shen et al (2016), especially in the development of behavioral skills and strategies that could eventually permeate the family environment.…”
Section: Perception Of Family Physical Activitymentioning
confidence: 99%
“…According to the ecological model, the second level of influence for promoting active behavior in children is that provided by parents (Shen et al, 2016). Within this level, different types of social support can be provided by mothers to motivate their children to be active, such Revista Electrónica Educare (Educare Electronic Journal) EISSN: 1409-4258 Vol.…”
Section: Different Types Of Support That Mothers Can Provide To Theirmentioning
confidence: 99%